Gold and Cobalt Oxide Nanoparticles Modified Poly-Propylene Poly-Ethylene Glycol Membranes in Poly (ε-Caprolactone) Conduits Enhance Nerve Regeneration in the Sciatic Nerve of Healthy Rats - Derya Burcu Hazer Rosberg (International Journal of Molecular Sciences, 2021)
Reconstruction of nerve defects is a clinical challenge. Autologous nerve grafts as the gold standard treatment may result in an incomplete restoration of extremity function. Biosynthetic nerve conduits are studied widely, but still have limitations. Here, we reconstructed a 10 mm sciatic nerve defect in healthy rats and analyzed nerve regeneration in poly (ε-caprolactone) (PCL) conduits longitudinally divided by gold (Au) and gold-cobalt oxide (AuCoO) nanoparticles embedded in poly-propylene poly-ethylene glycol (PPEG) membranes (AuPPEG or AuCoOPPEG) and compared it with unmodified PPEG-membrane and hollow PCL conduits. After 21 days, we detected significantly better axonal outgrowth, together with higher numbers of activated Schwann cells (ATF3-labelled) and higher HSP27 expression, in reconstructed sciatic nerve and in corresponding dorsal root ganglia (DRG) in the AuPPEG and AuCoOPPEG groups; whereas the number of apoptotic Schwann cells (cleaved caspase 3-labelled) was significantly lower. Furthermore, numbers of activated and apoptotic Schwann cells in the regenerative matrix correlated with axonal outgrowth, whereas HSP27 expression in the regenerative matrix and in DRGs did not show any correlation with axonal outgrowth. We conclude that gold and cobalt-oxide nanoparticle modified membranes in conduits improve axonal outgrowth and increase the regenerative performance of conduits after nerve reconstruction.